Edukasi Ibu Hamil Trimester III tentang Tanda Bahaya Bayi Baru Lahir di Desa Matang Puntong Kecamatan Samudera Kabupaten Aceh Utara - Elizar Elizar; Jasmiati Jasmiati; Hendrika Wijaya Kartini Putri; Nova Sumaini Prihatin (Jurnal Abdimas Kesehatan (JAK), 2023)
The neonatal period is the most critical period for the survival of a child. Based on data from the Central Statistics Agency (BPS), infant mortality under five years old in Indonesia reached 28,158 in 2020, while in Aceh in 2020 it was 8 per 1,000 live births with 792 cases of neonatal deaths and 49 cases originating from North Aceh. , with the most causes being pneumonia, namely 30 cases followed by diarrhea with 14 cases. Based on previous research, it was stated that the majority of mothers chose to take action/medication themselves when their children were sick, with the majority choosing to take them to health care facilities. The problem-solving method used in community service activities in Matang Puntong Village, Samudera Subdistrict, North Aceh Regency is to educate through presentations about danger signs for newborns and distributing leaflets and posters containing danger signs for newborns. The entire target audience, namely pregnant women in their third trimester, totaling 11 people attended the activity and there was an increase in the knowledge of the target audience for community service. It can be seen that in the pretest evaluation before participating in counseling activities 9% were in the good category and the post test evaluation score was 91% in the good category. It is important for health workers to continue to provide information about danger signs in newborns as an effort to increase mothers' knowledge so that they can immediately take action on the conditions that occur in their babies